2014
DOI: 10.1155/2014/746138
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Repair and Subchondral Bone Migration Using 3D Printing Osteochondral Composites: A One-Year-Period Study in Rabbit Trochlea

Abstract: Increasing evidences show that subchondral bone may play a significant role in the repair or progression of cartilage damage in situ. However, the exact change of subchondral bone during osteochondral repair is still poorly understood. In this paper, biphasic osteochondral composite scaffolds were fabricated by 3D printing technology using PEG hydrogel and β-TCP ceramic and then implanted in rabbit trochlea within a critical size defect model. Animals were euthanized at 1, 2, 4, 8, 16, 24, and 52 weeks after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 53 publications
1
53
0
1
Order By: Relevance
“…A schematic of this process is shown in figure 4. Findings of this study revealed increased levels of collagen type I and type II formation as well as increased glycosaminoglycan and DNA production when compared to samples without printed chondrocytes [67]. In vitro results show promise as a hybrid approach for repairing articular cartilage.…”
Section: D Printing and Nanomaterials For Vascularized Bone Cartilamentioning
confidence: 89%
See 2 more Smart Citations
“…A schematic of this process is shown in figure 4. Findings of this study revealed increased levels of collagen type I and type II formation as well as increased glycosaminoglycan and DNA production when compared to samples without printed chondrocytes [67]. In vitro results show promise as a hybrid approach for repairing articular cartilage.…”
Section: D Printing and Nanomaterials For Vascularized Bone Cartilamentioning
confidence: 89%
“…Researchers continue to struggle with the balance of biocompatibility, bioactivity, and acceptable mechanical properties of 3D printed implants. Currently, no effective scaffold has been fabricated to recapitulate the zonal organization, extracellular matrix composition, and mechanical properties of native load bearing cartilage, like that found within articulating joints [67]. Conversely, recent successes in non-load-bearing regions provide insight and promise of progress for this challenging tissue moving forward.…”
Section: D Printing and Nanomaterials For Vascularized Bone Cartilamentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Zhang et al [18] fabricated PEG/β-TCP OC scaffolds using, as in previous work, SL and gel casting. However, unlike the previous approach, the authors produced a β-TCP ceramic scaffold using the gel casting process, while for the chondral zone it was used SL.…”
Section: Stereolithographymentioning
confidence: 99%
“…For example, hydroxyapatite has been printed with a porous polylactide (PLA) scaffold to mimic the osteochondral tissue composition and in vivo results exhibited osteogenic and chondrogenic markers in both respective layers [45] . Similarly, stereolithography process has been used to fabricate osteochondral constructs with polyethylene glycol and beta (β)-tricalcium phosphate, which showed encouraging results in a year-long follow-up study in a rabbit critical-size defect model [46] . Using fused deposition modeling, Cao et al fabricated a honey-comb-like PCL scaffold with 0°/60°/120° lay-down pattern to create anisotropic structures [47] .…”
Section: Three Dimensional (3d) Printing For Osteochondral Defect Heamentioning
confidence: 99%